Male students and digital game: reason, motivation and feeling - Mat Sin, Nazirah; Talib, Othman; Tenku Shariman, Tengku Putri Norishah; Ishak, Adura Azlin; Baki, Roselan (International Association of Computer Science and Information Technology (I A C S I T), 2014)
The games industry has become one of the most lucrative industries in the world due to the billion dollar sales of digital games. Digital game play is like a culture among majority of students in high schools, especially males who play games every day. This phenomenon has stimulated researchers and academics to further study the various contexts of gaming. This preliminary study has identified the motivating factors of certain games that were able to sustain the interest of five male students in playing those digital games. A basic qualitative research design is adopted as the research method. The findings has reported – five motivating factors which are type of game, content, challenge, control, update and fun that incite students to consistently play the digital games.